(untitled) (The Review of Diabetic Studies, 2025)
Background Chronic nasal obstruction (CNO) is a prevalent condition that can significantly affect upper airway physiology and sleep quality. Emerging evidence suggests a strong association between nasal airflow limitation—caused by chronic rhinosinusitis (CRS), allergic rhinitis, or structural abnormalities—and sleep-disordered breathing (SDB), including obstructive sleep apnea (OSA). This systematic review aimed to synthesize current evidence on the impact of CNO on sleep quality, OSA risk, and related physiological and psychosocial outcomes in adults. Methods This review followed the PRISMA 2020 guidelines. Searches were performed in PubMed, Scopus, Web of Science, Embase, and Google Scholar between January 2015 and June 2024. Eligible studies included adult participants (≥18 years) with nasal obstruction due to CRS, allergic rhinitis, or anatomical deformity and reported objective or subjective sleep outcomes such as apnea–hypopnea index (AHI), PSQI, or Epworth Sleepiness Scale (ESS). Data were extracted and narratively synthesized due to study heterogeneity. Quality appraisal was conducted using the Newcastle–Ottawa Scale and Cochrane RoB 2 tools. Results Ten studies met inclusion criteria. Across designs, nasal obstruction was consistently associated with impaired sleep quality and increased OSA risk. CRS patients showed significantly higher STOP-Bang, ESS, and PSQI scores than controls. Allergic rhinitis nearly doubled OSA risk (pooled OR ≈ 1.9). Surgical or medical interventions that improved nasal patency, such as functional endoscopic sinus surgery, led to measurable improvements in both subjective and objective sleep parameters. Smoking, inflammation, and structural abnormalities exacerbated these relationships, while psychological distress mediated perceived sleep impairment in several cohorts. Conclusion Evidence strongly supports chronic nasal obstruction as an independent and modifiable contributor to poor sleep quality and OSA development in adults. Nasal patency restoration—through medical, surgical, or behavioral interventions—may yield substantial improvements in sleep health, mood, and quality of life.